Methodology of pedagogical research between normativity and descriptivity - Kubinowski, Dariusz (Methodological critique in the practice of knowledge creation, 2019)
The author tries to identify, present and explain permanent controversies concerning three key methodological categories used in the methodology of pedagogical research in Poland: “pedagogical dimension” of scientific research; scope of pedagogical research; and methodology in pedagogical research. The author describes the nature of the controversy and emphasizes his own approach to it. The main aim of the chapter is to propose the author’s own concept of understanding the methodology of pedagogical research as philosophical-empirical science that is built and being constantly rebuilt in diachronic and dialectic relationships between normative and descriptive methodologies, as an emergent reaction to radical and dynamic changes of a social reality. The author emphasizes the important role of methodological research (“research on research”) in constructing new scientific knowledge in the field of methodology of pedagogical research.